(untitled) (Proceedings of International Conference on Special Education, 2025)
Utilizing the descriptive research design, integrating the Research & Development (R&D) methodology, this study developed the Pre-kindergarten Transition Program (PTP) for Child Development Workers (CDWs) based on the identified the factors that affect common adjustment issues of pre-kindergartners and the various experiences of CDWs in handling adjustment issues during transition period. The study was conducted in the five districts of Child Development Centers (CDCs) in Laoag City. Using purposive sampling technique, this study involved 19 CDWs and three experts in the field of early childhood education (ECE). A structured interview guide for the Focus Group discussion (FGD) and a validation tool adapted from Valdez (2023) were used in gathering data. Data gathered from the FGD were analyzed using Braun and Clark’s (2006) thematic analysis while mean was used to determine the validity of the PTP. Findings reveal that the factors that affect the common adjustment issues of pre-kindergartners during transition period are lack of social exposure, separation anxiety, time and routine adjustments, and excessive use of gadgets at home. On the other hand, the CDWs employ interactive learning activities, open communication, and parental involvement and support in handling adjustment issues during transition period. Findings also reveal that the developed PTP is highly valid in terms of objectives (3.77), content (3.88), staff/persons involved (3.66), duration (4.00), and assessment/evaluative technique (3.78) along with the overall mean of 3.82. Thus, the PTP is recommended to be implemented to capacitate the CDWs in managing effectively the common adjustment issues of pre-kindergartners during transition period.